Repercussões jurídicas do uso da jurimetria digital ante o princípio da segurança jurídica: influência, controle, privacidade - Lima, Alexsandra de (2023)
Digital Jurimetry represents the adoption of novel techniques and technological tools by the field of Law, leading to a more efficient processing of data, aiding in the process of achieving the desired goals. It is becoming indispensable for legal professionals in terms of offering a service with a qualitative and quantitative emphasis. The support provided by this field of knowledge covers the elaboration of public policies, legislative review, the adaptation of potentially overruled judicial precedents in decision-making, elaboration of legal procedural strategy, among others. The use of jurimetry generates vast legal repercussions. Three major results were perceived with the use of Digital Jurimetry: the potential influence in decision-making, the manipulation of jurisprudence in favor certain legal theses, and the profiling judges with the use of personal data, which was received diversified by two countries: Brazil and France. Throughout the research, it is clear, however, that the use of Digital Jurimetry as a tool in judicial bodies has not been widely adopted. It is primarily used in private law firms, with marginal adoption in public institutions. State bodies adopt, instead, initiatives aimed at the development of artificial intelligence models to achieve their goals. Despite this, the study is justified by the novelty of the theme, as well as by the ongoing divergence between Digital Jurimetry and similar fields such as analytics and juscibernetics. The adopted methodology follows the exploratory scientific method, seeking to improve ideas on the subject, deductive, starting from the general to the particular, it is essentially pure, since it aims to improve scientific theories, of a descriptive nature, as it details the institutes involved in the study and, procedurally, bibliographical, having the literature on the subject as support. From historical and conceptual data, it is possible to reach important conclusions regarding the importance of this field that still depends on regulation to guarantee the maximum social benefit, as well as all the legal security that one seeks to obtain with its use.